Application of Standard Costs in the Business Sector: A Literature Review (1991-2023) (Ágora de Heterodoxias, 2024)
The aim of this update article is to understand the degree of application of standard costs in the business sector worldwide, conducting a literature review from 1991 to 2023; based on the thesis that a cost system is a fundamental aspect for companies, its determination is the responsibility of management, which expects to obtain timely and adequate information through it, allowing the achievement of established goals. Methodologically, a descriptive, quantitative, and documentary approach was used to analyze different articles where surveys were conducted with entrepreneurs to learn about the use of standard costs, their advantages, and additional contemporary tools used in conjunction. The main finding indicates that the degree of application of standard costs is significant worldwide, with usage rates reaching 90% in the United Kingdom and 77% in Dubai, respectively. Advantages of using standard costs include: budgetary and management control, aid in decision-making, and cost reduction; it is also substantial to indicate that, together with standards, Activity-Based Costing (ABC), Just In Time (JIT), Total Quality Management (TQM), Balanced Scorecard (BSC), Lean Manufacturing, and the Theory of Constraints (TOC) are used.
Keywords: costs; production control; resource management; decision-making